PENGGUNAAN APLIKASI KEYMAN PADA SMARTPHONE DALAM PEMBELAJARAN MENULIS AKSARA BALI DI KELAS X SMA NEGERI 3 AMLAPURA - I Wayan Adi Upadana; Ni Komang Aryani (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2023)
Balinese language learning cannot be separated from the existence of Balinese language, literature and script. Learning Balinese script in schools must be applied as interestingly as possible. Writing Balinese script in general can use paper, palm and computer/smartphone media. Especially for Balinese writing material, the learning process must be packaged as interesting as possible. This is done to motivate students to learn to recognize and understand the use of Balinese Script. In this case, writing Balinese Script can be done on a Smartphone using the keyman application. This application is quite easy to use by students at SMA Negeri 3 Amlapura. The use of this application aims to facilitate the learning process of digitizing Balinese characters because in the process everything can be accessed through a Smartphone. The results of the application of the keyman application in learning Balinese script, students responded positively. Students began to understand the development of digitization of the Balinese script. The positive impact obtained is that they are happy to use the application. By using this keyman application, students are easier to learn and apply it in everyday life.